Connections between microhabitat factors and dimensions of brown trout (Salmo trutta) redds - Atique, Faiqa (2017)
This study is part of a process of habitat restoration and management of Finnish and Swedish rivers. This study was conducted to analyse detailed and generalised data regarding microhabitat factors and dimensions of spawning redd of brown trout (salmo trutta). The objectives of this study were to analyse connections between redd dimensions, connections between redd length and microhabitat factors and to analyse the variability of redd length and microhabitat factors among catchments in order to understand spawning habitat selectivity of brown trout (salmo trutta). The study shows that the redd dimensions are positively and strongly correlated. Redd length is weakly correlated to microhabitat factors: Redd length correlates positively to dominate and sub dominate particle size category in pot but does not correlate with dominate particle size category upstream from pot. Microhabitat is catchment specific. If I assume redd length as a proxy of fish size it can be speculate that not only fish size influence fish choice for spawning microhabitat but also other factors are involved. Modeling regarding redd dimensions and spawning microhabitat factors can be helpful to improve strategies for habitats restoration process.